2003
DOI: 10.1037/0278-6133.22.2.148
|View full text |Cite
|
Sign up to set email alerts
|

Psychological factors associated with fruit and vegetable intake and with biomarkers in adults from a low-income neighborhood.

Abstract: Fruit and vegetable consumption is below recommended levels in the population, paricularly in low-income groups. This study assessed factors associated with self-reported intake and 2 biomarkers (potassium excretion and plasma vitamin C) in 271 adults living in a low-income neighborhood. Attitudinal barriers to change were negatively related to reported intake and to potassium excretion. Poor knowledge of recommended consumption was associated with low reported intake, low potassium excetion, and low plasma vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(100 citation statements)
references
References 51 publications
1
97
1
Order By: Relevance
“…Research shows that chance health locus of control (belief that good health is a result of chance) is consistently related to being of lower socio-economic status and the higher likelihood of healthcompromising behaviours, such as smoking, sedentary lifestyles and poorer diet (40) . Women of lower educational attainment and low socio-economic status are more likely to feel that their future health is an inevitable consequence of chance rather than under their control (39,41) . Other research has shown that women with higher levels of education eat fruit and vegetables more frequently and believe less in chance and more in eating healthily as a way of maintaining their health (42,43) .…”
Section: Controlmentioning
confidence: 99%
“…Research shows that chance health locus of control (belief that good health is a result of chance) is consistently related to being of lower socio-economic status and the higher likelihood of healthcompromising behaviours, such as smoking, sedentary lifestyles and poorer diet (40) . Women of lower educational attainment and low socio-economic status are more likely to feel that their future health is an inevitable consequence of chance rather than under their control (39,41) . Other research has shown that women with higher levels of education eat fruit and vegetables more frequently and believe less in chance and more in eating healthily as a way of maintaining their health (42,43) .…”
Section: Controlmentioning
confidence: 99%
“…First, the measurement of dietary consumption was self-reported which can cause bias as people may miss calculation of consumed portions in the previous weeks and may hold biased views about their own eating patterns. In spite of such potential bias, dietary self-reports have been validated against objective assessment such as biomarkers (30) . Second, there was an increase in self-reported healthy nutrition over time but the overall efficacy of the treatment could not be evaluated because this was not a randomized controlled trial, and no control group was available.…”
Section: Discussionmentioning
confidence: 99%
“…It would not be correct to state that less vegetable consumption is a sign of a low income because low vegetable consumption is considered as a more complex problem with the combined effect of several factors such as motivation, psychology, or lifestyle. Therefore, providing consumers with information about the energy, vitamin, and mineral content and recommended intake of vegetables is considered to be highly beneficial (Steptoe et al, 2003). Moreover, people should be motivated to increase their intake of vegetables for a healthier diet (Dibsdall et al, 2003).…”
Section: Discussionmentioning
confidence: 99%